2021
DOI: 10.24925/turjaf.v9i4.822-828.4265
|View full text |Cite
|
Sign up to set email alerts
|

Fig Vinegar as an Antioxidant and Antimicrobial Agent

Abstract: Fig vinegar is a special product which has a long history and is handed down from generation to generation. In the current study, characteristics of homemade fig vinegars supplied from different cities of Turkey were compared in terms of their physicochemical, antioxidant and antimicrobial properties. Physicochemical properties of the samples were very diverse. Total phenolic and flavonoid content, and ABTS+ and DPPH radical scavenging activities of the samples were ranged from 313.5 to 594.25 mg GAE/L and 42.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This phenomenon may be associated with the probable extraction of compounds from the wood of the acetification barrel, associated with the chemical composition of these vinegars, which present differences in the concentrations of phenolic compounds compared to pulp vinegar. The color properties of different types of vinegar can change depending upon the color of the raw material and the technology used in the production 54 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon may be associated with the probable extraction of compounds from the wood of the acetification barrel, associated with the chemical composition of these vinegars, which present differences in the concentrations of phenolic compounds compared to pulp vinegar. The color properties of different types of vinegar can change depending upon the color of the raw material and the technology used in the production 54 .…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial potential. Vinegar has been recognized as an antimicrobial substance for a long time, and several studies have shown vinegars of different origin can act as antimicrobial agents against different www.nature.com/scientificreports/ pathogens 54 . Table 5 shows the results of the susceptibility of different bacterial strains (gram-negative and grampositive) and yeasts to the pulp and peel vinegar produced in the present work.…”
Section: Acetic Fermentation and Pineapple Pulp And Peel Vinegars: Ph...mentioning
confidence: 99%
“…This phenomenon may be associated with the probable extraction of compounds from the wood of the aceti cation barrel, associated with the chemical composition of these vinegars, which present differences in the concentrations of phenolic compounds compared to pulp vinegar. The color properties of different types of vinegar can change depending upon the color of the raw material and the technology used in the production 49 .…”
Section: Fermentation Parametersmentioning
confidence: 99%
“…Vinegar has been recognized as an antimicrobial substance for a long time, and several studies have shown vinegars of different origins can act as antimicrobial agents against different pathogens 49 . Table 5 shows the results of the susceptibility of different bacterial strains (gram-negative and gram-positive) and yeasts to the pulp and peel vinegar produced in the present work.…”
Section: Antimicrobial Potentialmentioning
confidence: 99%